Cultural inclusivity and corporate social responsibility in China - Guangfan Sun; Changwei Guo; Bin Li; Honglei Li (Humanities & Social Sciences Communications, 2023)
Abstract This paper aims to explore whether cultural inclusivity has a significant impact on corporate social responsibility (CSR). The research shows that firms located in regions with higher cultural inclusivity tend to take on more social responsibilities, suggesting that corporate humanistic care and environmental awareness are linked to cultural inclusivity. Furthermore, the effect of cultural inclusivity is more evident in large firms, state-owned enterprises, and firms with high board independence. The use of natural disasters as an instrumental variable in the analysis helped to address endogeneity concerns. Additionally, the outcomes indicate that regions with greater exposure to cultural inclusivity tend to exhibit more characteristics of “gender equality” and fewer characteristics of “power gap”, which have a strong correlation with CSR. These findings shed light on the impact of cultural inclusivity on corporate governance and help explore the informal institutional factors influencing CSR at the geographical level.